2019
DOI: 10.1186/s40066-018-0245-6
|View full text |Cite
|
Sign up to set email alerts
|

Yield loss of ginger (Zingiber officinale) due to bacterial wilt (Ralstonia solanacearum) in different wilt management systems in Ethiopia

Abstract: Background: Ginger bacterial wilt is the most destructive disease that causes qualitative and quantitative rhizome yield losses in Ethiopia. Field studies were conducted to assess yield loss caused by bacterial wilt of ginger in different wilt management systems at Teppi and Jimma, Ethiopia, during 2017. Management systems were host resistance (Boziab and Local) and cultural practices (lemon grass, potassium fertilizer and soil solarization), which were applied as sole and in different levels of integrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 21 publications
4
28
0
1
Order By: Relevance
“…Ginger, a herbaceous tropical perennial crop, belongs to the family Zingiberaceae [20]. Among the diseases that affect ginger, bacterial wilt caused by R. solanacerum is one of the major production constraints in several regions of the world [21]. Even though there are several released varieties in ginger, none of them is resistant to R. solanacearum infection due to lack of genetic variability.…”
Section: Strategies To Reveal the Disease-resistant Mechanism Of Mango Gingermentioning
confidence: 99%
“…Ginger, a herbaceous tropical perennial crop, belongs to the family Zingiberaceae [20]. Among the diseases that affect ginger, bacterial wilt caused by R. solanacerum is one of the major production constraints in several regions of the world [21]. Even though there are several released varieties in ginger, none of them is resistant to R. solanacearum infection due to lack of genetic variability.…”
Section: Strategies To Reveal the Disease-resistant Mechanism Of Mango Gingermentioning
confidence: 99%
“…(Habetewold et al, 2015 andTariku et al, 2016). Recently, ginger bacterial wilt is the most destructive disease that causes qualitative and quantitative rhizome yield losses in Ethiopia (Merga et al, 2019). In Ethiopia, almost 90% ginger production had been devastated because of this disease (Habetewold et al, 2015;Tariku et al, 2016).…”
Section: Weed Disease and Insect Pestsmentioning
confidence: 99%
“…Combined application of diverse methods such as host resistance, cultural practices, and biological and chemical control in integrated disease management schemes is recommended to control some level of bacterial wilt (Merga et al, 2019). Also, Nybe et al (2007) reported that, selection of disease free rhizomes, soil and rhizome solarization, crop rotation, hot water treatment of rhizome (50°C for 10 min or 40°C for 15 min), using animal dung (farmyard manure), etc.…”
Section: Weed Disease and Insect Pestsmentioning
confidence: 99%
“…Ralstonia solanacearum (Rs) [2] is a soil-borne bacterium that infects plant roots and ultimately causes susceptible plants to wilt and die. Bacterial wilt caused by Rs [2] is a major threat to crop production around the world [15,18,34]. In the United States, some of the most important vegetable crops, such as tomatoes and potatoes [1], can suffer significant yield loss from bacterial wilt [3,34].…”
Section: Introductionmentioning
confidence: 99%